Isotype Heterojunction-Boosted CO2 Photoreduction to CO - Ban, Chaogang; Duan, Youyu; Wang, Yang; Ma, Jiangping; Wang, Kaiwen; Meng, Jiazhi; Liu, Xue; Wang, Cong; Han, Xiaodong; Cao, Guozhong; Gan, Liyong; Zhou, Xiaoyuan (Nano-Micro Letters, 2022)
Photocatalytic conversion of CO2 to high-value products plays a crucial role in the global pursuit of carbon–neutral economy. Junction photocatalysts, such as the isotype heterojunctions, offer an ideal paradigm to navigate the photocatalytic CO2 reduction reaction (CRR). Herein, we elucidate the behaviors of isotype heterojunctions toward photocatalytic CRR over a representative photocatalyst, g-C3N4. Impressively, the isotype heterojunctions possess a significantly higher efficiency for the spatial separation and transfer of photogenerated carriers than the single components. Along with the intrinsically outstanding stability, the isotype heterojunctions exhibit an exceptional and stable activity toward the CO2 photoreduction to CO. More importantly, by combining quantitative in situ technique with the first-principles modeling, we elucidate that the enhanced photoinduced charge dynamics promotes the production of key intermediates and thus the whole reaction kinetics. Highlights: 1 The g-C3N4 isotype heterojunction was synthesized for photocatalytic CO2 reduction, which exhibits an impressive activity and outstanding stability. 2 The isotype heterojunction presents more favorable charge separation and transfer performance than the single components. 3 The enhanced photogenerated charge dynamics in isotype heterojunction facilitates the production of key intermediates and thus the whole reaction kinetics.